2020
DOI: 10.1177/0009922820928054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Personalized Audit and Feedback Intervention on Antibiotic Prescribing Practices for Outpatient Pediatric Community-Acquired Pneumonia

Abstract: Antibiotic choice for pediatric community-acquired pneumonia (CAP) varies widely. We aimed to determine the impact of a 6-month personalized audit and feedback program on primary care providers’ antibiotic prescribing practices for CAP. Participants in the intervention group received monthly personalized feedback. We then analyzed enrolled providers’ CAP antibiotic prescribing practices. Participants diagnosed 316 distinct cases of CAP (214 control, 102 intervention); among these 316 participants, 301 received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Likewise, in an outpatient study from the USA, personalised audits and feedback interventions were able to steer antibiotic prescribing practices for 316 children with community-acquired pneumonia, which is a rather common but however limited problem [ 25 ]. The intervention group had fewer (5.9%) non-guideline-concordant antibiotics prescribed, compared to 21.4% in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in an outpatient study from the USA, personalised audits and feedback interventions were able to steer antibiotic prescribing practices for 316 children with community-acquired pneumonia, which is a rather common but however limited problem [ 25 ]. The intervention group had fewer (5.9%) non-guideline-concordant antibiotics prescribed, compared to 21.4% in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although many guidelines have been published on how to treat LRTIs in children, very few studies have looked at how successfully the guidelines have been implemented 7,12,20 . One American study evaluated the impact of a 6‐month personalised audit and feedback programme on how primary care providers issued prescriptions for antibiotics for paediatric CAP 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zahlanie et al 63 showed that implementation of computerized treatment pathways in addition to personalized education sessions for primary care providers resulted in a substantial increase in the proportion of first‐line antibiotic prescriptions and reduction of antibiotic duration for children with a bacterial acute respiratory infection (ARI), and seeking medical attention in outpatient settings compared to the control group. A recently published report by Diaz et al 64 showed successful utilization of personalized scheduled audit and feedback to outpatient providers with the improvement of antibiotic prescriptions for community‐acquired pneumonia. Another research team was able to successfully reduce inappropriate use of oral third‐generation cephalosporins in children seen in ambulatory settings after implementation of intermittent education and audit with feedback from the antimicrobial stewardship team 65 .…”
Section: Benefits Of Antimicrobial Stewardship In Pediatricsmentioning
confidence: 99%